Feasible routing selection mechanism in multichannel wireless networks. Issue 5 (1st February 2014) - Zhang, Fan; Cao, Yewen
Abstract : Considering more practical scenarios in the designing of joint routing, channel‐assignment and scheduling algorithms in multichannel wireless networks, a modified routing selection scheme based on a performance guaranteed MP mechanism is put forward. The assumption made in MP, that the balance factor chosen for each link αl = α for all links l is not reasonable, is pointed out and may influence the performance of MP badly in the case of channels with large diversity. Focusing on this point, a balance factor used for channel assignment in MP is taken into account in the stage of route selection and the limitation of original MP is relaxed. As a result, the proposed joint algorithm is able to better adapt to the condition of channels with large diversity. It is proved that the modified policy for MP is able to achieve the same capacity region as that of original MP.